2013
DOI: 10.1128/jvi.00776-13
|View full text |Cite
|
Sign up to set email alerts
|

Complex Reassortment of Multiple Subtypes of Avian Influenza Viruses in Domestic Ducks at the Dongting Lake Region of China

Abstract: bTo gain insight into the ecology of avian influenza viruses (AIV), we conducted active influenza virus surveillance in domestic ducks on farms located on the flyway of migratory birds in the Dongting Lake region of Hunan Province, China, from winter 2011 until spring 2012. Specimens comprising 3,030 duck swab samples and 1,010 environmental samples were collected from 101 duck farms. We isolated AIV of various HA subtypes, including H3, H4, H5, H6, H9, H10, H11, and H12. We sequenced the entire coding sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 74 publications
(91 reference statements)
3
61
0
Order By: Relevance
“…Swab samples from different species of poultry (chicken, duck, and pigeon) and environmental samples (fresh poultry feces, cage swabs, and sewage) were collected from each poultry booth. Data collection methods for swab sample collection have been described elsewhere (9). Briefly, a cloacal swab and a tracheal swab from the same bird were placed in the same sample collection tube and counted as one sample, and all of the poultry swab samples were collected from apparently healthy poultry (9).…”
Section: Methodsmentioning
confidence: 99%
“…Swab samples from different species of poultry (chicken, duck, and pigeon) and environmental samples (fresh poultry feces, cage swabs, and sewage) were collected from each poultry booth. Data collection methods for swab sample collection have been described elsewhere (9). Briefly, a cloacal swab and a tracheal swab from the same bird were placed in the same sample collection tube and counted as one sample, and all of the poultry swab samples were collected from apparently healthy poultry (9).…”
Section: Methodsmentioning
confidence: 99%
“…Reassortment between human H1N1 and H3N2 lineages is detected more rarely but gave rise to an H1N2 virus that circulated widely in the United Kingdom in 2001-2002 (20, 21). Reassortment among avian influenza viruses in birds is highly prevalent and has a major impact on viral population structure in avian reservoirs (22)(23)(24)(25)(26)(27)(28)(29)(30). Thus, reassortment between IAV from two distinct sources occurs in nature and can have major consequences for the epidemiology of the virus in humans and other natural hosts.…”
mentioning
confidence: 99%
“…H5N1 influenza viruses that have been detected in ducks in this region are complicated reassortants that have progressively acquired the ability to infect and kill mammals (30,31). Surveillance studies have revealed the existence of different subtypes of H6 viruses in the live poultry markets in southern China (32)(33)(34)(35)(36), which is where the H5N1 influenza viruses and H7N9 viruses jumped to humans. Although a vast amount of sequence analysis of the H6 viruses has been performed (25,(32)(33)(34)(35)(36)(37)(38)(39), there has been relatively little biologic characterization of the H6 viruses from China.…”
mentioning
confidence: 99%
“…Surveillance studies have revealed the existence of different subtypes of H6 viruses in the live poultry markets in southern China (32)(33)(34)(35)(36), which is where the H5N1 influenza viruses and H7N9 viruses jumped to humans. Although a vast amount of sequence analysis of the H6 viruses has been performed (25,(32)(33)(34)(35)(36)(37)(38)(39), there has been relatively little biologic characterization of the H6 viruses from China. Here, we fully characterized the genetic variation, receptor-binding specificity, replication capability, and transmission in mammals of a series of H6 influenza viruses that were detected in the live poultry markets in southern China between 2008 and 2011.…”
mentioning
confidence: 99%